PEMBERIAN ZAT BESI PADA IBU HAMIL DAN HASIL LUARAN BAYI: LITERATURE REVIEW - Noor Azizah; Dwi Astuti; Indanah Indanah (Universitas Muhammadiyah Kudus, 2023)
Background: One factor of perinatal mortality is caused by low birthweight. Factors affecting babies with low birth weight from the intake of folic acid, iron. The nutritional status of pregnant women that is not fulfilled causes anemia so that it has a risk of low birthweight.Objective: This study aims to provide the effect of supplementation with infant outcomesMethod: The research method is scoping review with PRISMA approach. Search using electronic databases such as PubMed, Science Direct and Scopus. Literature review is carried out in international journals published within the last 5 years, full text, and not the results of review.Results: Prevention of anemia by giving blood-added tablets containing iron and folic acid is very important in pregnant women. Moderate and severe anemia in pregnant women can result in the risk of low birth weight, prematurity, growth retardation in the uterine, fetal distress, asphyxia, stillbirth.Conclusion: Giving blood-added tablets and education to pregnant women related to adherence to taking blood-added tablets is very important for the prevention of anemia in pregnancy so as to produce normal baby outcomes.